Knowledge governance processes and perspectives - Foss, Nicolai J., 1964-; Michailova, Snejina, 1965- (Oxford : Oxford University Press, 2009)
While there are many books on knowledge management, knowledge governance is a concept that has not been so well explored, and is much less understood. Knowledge governance refers to choosing structures and mechanisms that can influence the processes of sharing and creating knowledge.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Intellectual capital -- Management; Knowledge workers -- Management; Knowledge management; Organizational change; Organization